Prevalencia y factores asociados a prescripción potencialmente inapropiada en adultos mayores atendidos en el Hospital Apoyo Iquitos, 2024 - Castillo Rengifo, José Manuel (2025)
Introduction: Population aging leads to a progressive decline in functionality, impacting medical treatment and promoting potentially inappropriate prescribing (PIP) and polypharmacy, which increases the risk of adverse drug reactions and severe drug interactions. Objectives: To determine the prevalence and factors associated with potentially inappropriate prescription in older adults treated in the medical hospitalization of the Hospital Apoyo Iquitos in 2024. Methodology: This was an analytical observational study with a cross-sectional and retrospective design. Population: Included 193 older adult patients aged 65 and over, with a sample consisting of 127 patients. Results: A total of 63.8% of patients received at least one PIP according to the STOPP/START criteria. Prolonged hospital stay was a significant factor (p = 0.003, aOR = 1.338), increasing the probability of PIP by 33% for each additional day of hospitalization. Polypharmacy showed a significant association (p = 0.009, aOR = 2.155), indicating that the use of five or more drugs doubles the risk of PIP. The Charlson comorbidity index was the strongest predictor (p = 0.000, aOR = 10.001), suggesting that a higher disease burden increases the probability of PIP tenfold. In contrast, age (p = 0.333), sex (p = 0.324), education level (p = 0.294), and place of origin (p=0.302) were not significant predictors. Conclusion: PIP is common among hospitalized older adults and is associated with prolonged hospital stay, polypharmacy, and comorbidity burden, highlighting the importance of strategies to optimize prescribing in this population.